2020
DOI: 10.1061/(asce)st.1943-541x.0002604
|View full text |Cite
|
Sign up to set email alerts
|

Design of Structures That Adapt to Loads through Large Shape Changes

Abstract: Adaptive structures can modify their geometry and internal forces through sensing and mechanical actuation in order to maintain optimal performance under changing actions. Previous work has shown that wellconceived adaptive design strategies achieve substantial whole-life energy savings compared with traditional passive designs. The whole-life energy comprises an embodied part in the material and an operational part for structural adaptation. Structural adaptation through controlled large shape changes allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Future work could extend the design and control strategies given in this paper to consider actuators installed in parallel. Extensions of the control strategies presented in this work to include geometric non-linear shape control (Reksowardojo et al, 2020a) as well as consideration of dynamics could also be subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work could extend the design and control strategies given in this paper to consider actuators installed in parallel. Extensions of the control strategies presented in this work to include geometric non-linear shape control (Reksowardojo et al, 2020a) as well as consideration of dynamics could also be subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Highrise structures, long-span bridges and self-supporting roof systems are generally stiffness governed and therefore they are could greatly benefit from adaptive design strategies. Structural adaptation through geometric non-linear control has been further investigated in Reksowardojo et al (2019Reksowardojo et al ( , 2020a. Numerical and experimental studies have shown that when the structure is designed to be controlled into shape configurations that are optimal to counteract the effect of the external load, the stress can be effectively homogenized and minimized under different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Teuffel (2004) offers a first approach for truss structures, the load path management, which is built upon in Senatore et al (2019) to optimize the structure in regards to overall energy consumption using the integrated force method (Patnaik, 1973), resulting in a new integral formulation to optimize adaptive structure in regards to overall energy consumption. Reksowardojo et al (2020) presents a method for stress homogenization through large shape changes, i.e., geometric non-linearity, for trusses. In Wagner et al (2018) and Böhm et al (2019), Gramian-based approaches are described, which select actuated elements with the help of a greedy algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Structural adaptation is particularly beneficial for stiffness governed design problems such as slender high-rise structures, long-span bridges and selfsupporting roof systems. When the structure is designed to counteract the effect of loading through controlled large shape changes, further material and embodied energy savings are obtained compared to adaptive structures limited to small shape changes as well as to passive structures (Reksowardojo et al, 2019(Reksowardojo et al, , 2020. This way, the structure is controlled into optimal shapes as the external load changes so that the stress is significantly homogenized, and the design is not governed by strong loading events which occur rarely.…”
Section: Introduction Adaptive Structuresmentioning
confidence: 99%